Juvenile Justice in Indonesia: Analysis of Positive Law and Islamic Law - Edi Yaksa; T. Riza Zarzani; Fitri Rafianti (PT. Sinergi Legal Publisher, 2025)
The juvenile criminal justice system in Indonesia is specifically regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System as a form of lex specialis to the Criminal Procedure Code, which marks a shift in approach from a retributive system to a more restorative and rehabilitative system. This study aims to analyze how Indonesian positive law regulates juvenile justice and explore how Islamic law views the position of children who commit crimes. The study uses a normative juridical method with a statutory and conceptual approach, and is based on two main legal theories, namely John Rawls' Theory of Justice and Imam Al-Syathibi's Maqasid al-Syariah Theory. The results show that both Indonesian positive law and Islamic law have the same goal of protecting children's rights through educative and non-repressive mechanisms. However, there are philosophical differences in determining the limits of criminal responsibility, where positive law uses chronological age as a measure, while Islamic law emphasizes mental maturity (baligh). This study emphasizes the importance of synthesizing values ​​between the national legal system and Islamic legal principles to establish a juvenile justice system that is not only procedurally just, but also substantively and contextually just. The main conclusion of this study is that Indonesia needs to redesign its juvenile criminal law paradigm by integrating the principles of distributive justice and the spiritual values ​​of its society, so that the law becomes not merely a tool of power, but a vehicle for liberating children from the misleading logic of punishment